Language Laboratory Management to Support Technology-Based Foreign Language Instruction - Aulia, Vivi (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2016)
Language laboratory is one of media and teaching aids that cannot be separated from the foreign language teaching. The existence of language laboratory in such schools are considered as vital and essential things. It also becomes trend, culture, and alternative requirement to support the instructional process. Good and representative language laboratory that provides a number of educational objectives can bring in interesting instructional activities. Moreover, it can be the fascinating devices equipping students in learning foreign language. This article will review and provide a framework for some informations and overviews of language laboratory, the main principles and guidelines for managing language laboratory, and explain how these principles can be applied for foreign language teaching. At the end of this article, it is suggested that either foreign language teacher or language laboratory manager along with school principals cooperate in maximizing the language laboratory as a means of supporting technology-based foreign language instructions